PENGARUH WORK-LIFE BALANCE DAN ORGANIZATIONAL CULTURE TERHADAP TURNOVER INTENTION PADA PEKERJA GENERASI Z DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Damayanti, Monika; Khatimah, Husnul (Media Riset Bisnis Ekonomi Sains dan Terapan, 2025)
The purpose of this study is to determine whether work-life balance and organizational culture influence turnover intention among Generation Z workers, with employee engagement as a mediating variable. This research employs a quantitative method. The population in this study consists of Generation Z workers. The sampling procedure uses a purposive sampling technique, which selects samples based on specific criteria, resulting in 100 respondents. Data collection was conducted by distributing questionnaires via Google Forms. The data analysis method used is Partial Least Squares (PLS) analysis, performed with SmartPLS software. The results of this study indicate that work-life balance, organizational culture, and employee engagement have a negative and significant effect on turnover intention. Furthermore, work-life balance and organizational culture have a positive and significant effect on employee engagement. However, employee engagement is not proven to significantly mediate the relationship between work-life balance and organizational culture on turnover intention. Keywords : Work-life Balance, Organizational Culture, Employee Engagement, dan Turnover Intention.